Influencia del nivel de inserción ósea del diente soporte en el desplazamiento de PPR de extremidad libre mandibular asociada al implante oseointegrado - Verri, Fellippo Ramos [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Falcón-Antenucci, Rosse Mary; Pereira, João Antônio; Santiago Júnior, Joel Ferreira (Universidad Central de Venezuela, 2010)
The rehabilitation with mandibular distal extension removable partial dentures (DERPD) is complex and the use of implants has been improving the functioning of this approach. The insertion bony level around of the last support tooth is an aggravating factor, since it can harm the longevity of the treatment. Thus, the aim of this research was to evaluate the displacement tendency of a mandibular DERPD associated to an implant, with different insertion bony levels and different connections between the RPD and the support tooth, by finite element analysis. Eight models were made: MA - DERPD, incisal rest, no bony loss; MB - DERPD, distal plate, no bony loss; MC - DERPD, incisal rest, no bony loss, with implant and ERA system; MD - DERPD, distal plate, no bony loss, with implant and ERA system; ME - DERPD, incisal rest, bony loss; MF - DERPD, distal plate, bony loss; MG - DERPD, incisal rest, bony loss, with implant and ERA system; MH - DERPD, distal plate, bony loss, with implant and ERA system. Loads of 50 N in each peak were applied. Displacement maps were obtained and showed that implant favors this association and the bony loss harms the prognostic of the prosthesis. It is concluded that: the introduction of the implant with ERA system reduced the displacement tendency of the tooth and supporting structures; introduction of distal plate reduced the movement tendency of the support tooth; the decrease of the periodontal support didn't influence significantly the displacement tendency of the models with distal plate distal, but it influenced the models with distal incisal rest.

La rehabilitación con prótesis parcial removible de extremidad libre (PPREL) inferior es compleja y el uso de implantes han mejorado el funcionamiento de este tipo de aparato. El nivel de inserción ósea alrededor del último diente soporte es factor agravante, ya que puede comprometer la longevidad del tratamiento. Así, el objetivo de este estudio fue evaluar la tendencia al desplazamiento de una PPREL asociada al implante oseointegrado, con diferentes niveles de inserción ósea y diferentes conexiones entre la PPR y el diente soporte, a través del método del elementos finitos. Fueron confeccionados 8 modelos: MA - PPREL, apoyo incisal, inserción integra; MB - PPREL, placa distal, inserción integra; MC - PPREL, apoyo incisal, inserción integra, con implante y sistema ERA; MD - PPREL, placa distal, inserción integra, con implante y sistema ERA; ME - PPREL, apoyo incisal, pérdida ósea; MF - PPREL, placa distal, pérdida ósea; MG - PPREL, apoyo incisal, pérdida ósea, con implante y sistema ERA; MH - PPREL, placa distal, pérdida ósea, con implante y sistema ERA. Fueron aplicadas fuerzas verticales de 50 N en cada cúspide. Fueron obtenidos mapas de desplazamiento que mostraron que el implante favorece esta asociación y la pérdida ósea perjudica el pronóstico de la prótesis. Se concluyó que: la introducción del implante con sistema ERA disminuyó la tendencia al desplazamiento del diente y estructuras subyacentes; la introducción de la placa distal disminuyó la tendencia a desplazamiento del diente soporte; la disminución del periodonto de sustentación no influenció significativamente la tendencia al desplazamiento en los modelos con placa distal, pero influenció en los modelos con apoyo distal.
Keywords: Biomechanics; Finite element analysis; Removable partial denture; Dental implant; Dental stress analysis; Periodontal insertion; Biomecánica; Análisis de elemento finito; Prótesis parcial removible; Implante dentario; Análisis del estrés dental; Inserción periodontal